Government Financial Assets and Debt Sustainability - Henao Arbelaez, Camila; Sobrinho, Nelson (Washington, D.C. : International Monetary Fund, 2017)
Do government financial assets help improve public debt sustainability? To answer this question, we assemble a comprehensive dataset on government assets using multiple sources and covering 110 advanced and emerging market economies since the late 1980s. We then use this rich database to estimate the impact of assets on two key dimensions of debt sustainability: borrowing costs and the probability of debt distress. Government financial assets significantly reduce sovereign spreads and the probability of debt crises in emerging economies but not in advanced economies, and the effect varies with asset characteristics, notably liquidity. Government finacial assets also help discriminate countries across the distribution of sovereign spreads, thus signaling information about emerging economies' creditworthiness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet